Study Interactivity In Digital Narrative: Children Engagement And Enjoyment - Karimi, Arafeh (2010)
This study examined the experience of how Iranian children interact with the Quest Atlantis digital narrative and sought to discover they various enjoyment level by applying the use of the Instrinsic Motivation Inventory (IMI) instrument (Ryan, 2006)